Pengaruh Penggunaan Media Pembelajaran Berbasis Teknologi Terhadap Hasil Belajar Siswa Kelas V di Sekolah Dasar: The Effect of Technology-Based Learning Media on the Learning Outcomes of Fifth-Grade Students in Elementary Schools - Setiyawan, Hery; Aulia, Salwa Rizky; Firdaus, Nafilah Alifta; Putri, Ellena Aurellia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2024)
This study aims to examine the effect of technology-based learning media on the learning outcomes of fifth-grade students in elementary schools. The background of this research focuses on the importance of quality education in creating superior human resources. However, many learning processes still utilize monotonous methods, leading to low student interest and learning outcomes. Therefore, this research seeks to implement technology-based learning media as an alternative that can enhance student engagement and motivation. The research method employed is a quantitative method with and experimental design. Data were collected through tests of learning outcomes before and after the application of technology-based learning media. The results of the study are expected to show a significant positive effect of using such media on improving student learning outcomes. This research is anticipated to contribute to the development of more innovative and effective teaching methods, as well as enhance the quality of education in Indonesia.